Polyphenol content and antioxidant activity of phytoestrogen containing food and dietary supplements: DPPH free radical scavenging activity by HPLC - Klarić Daniela Amidžić; Mornar Ana; Kovačić Jelena; Jeličić Mario-Livio; Brusač Edvin; Brletić Iva; Klarić Ilija (Acta Pharmaceutica)
Soy, red clover, chaste tree, hop and flax have all been found to contain a wide range of phytoestrogenic compounds, and a large number of dietary supplements contain their extracts as principal ingredients. This study is aimed to evaluate the total polyphenolic content and antioxidant activity of phytoestrogen-containing food and formulated dietary supplements. The HPLC-DPPH method was applied for DPPH free radical scavenging activity testing of various phytoestrogen-containing samples. Polyphenol content and antioxidant activity in dietary supplements were higher than in functional food samples; multiple-botanical-source preparations showed higher polyphenol content and antioxidant activity than the mono-botanical counterparts. Furthermore, the correlation between polyphenol content and anti-oxidant activity was strongly statistically significant, so it might be concluded that antioxidant activity is proportional to the content of these secondary metabolites. The most striking batch-to-batch deviations were represented by one chaste berry-based product (RSD 41.3 %) and one red clover derived product (RSD 57.9 %). The results of this study contribute to a better understanding of the phenolic profile and antioxidant properties of phytoestrogen containing food and dietary supplements.